Empowered! = ¡Empoderados! : Latinos transforming Arizona politics - Magaña, Lisa; Silva, César S., 1982- (The University of Arizona Press, 2021)
"Empowered! examines Arizona's recent political history and how it has been shaped and propelled by Latinos. This book shows how Latinos are mobilizing to counter proposals for Draconian immigration laws with new and innovative approaches"--